Molecular docking: Bioactive compounds of Mimosa pudica as an inhibitor of Candida albicans Sap 3 - Gholam, Gusnia Meilin; Firdausy, Iman Akhyar; Artika, I Made; Abdillah, Ramadhani Malik; Firmansyah, Ridwan Putra; Irsal, Riyan Alifbi Putera; Zahra, Hafizh (IPB University, 2023)
Candida albicans (C. albicans) is a commensal microbiota that resides in humans. However, in certain cases, C. albicans can infect and cause several diseases to humans. This study aimed to investigate the interaction between Mimosa pudica bioactive compounds and C. albicans Sap 3. Molecular docking analysis was carried out using YASARA structure. The procedures involved preparation of ligands and target receptor, molecular docking, data analysis and visualization. All 3D ligands were downloaded from PubChem NCBI, while target receptor was downloaded from RCSB PDB. The interaction between Mimosa pudica bioactive compounds against Sap 3 resulted in a binding energies ranges from 5,168 – 7,480 kcal/mol and most of the interactions formed were relatively strong. Furthermore, the test ligands had contact with the catalytic residues and substrate binding site pockets S1/S2/S3/S4 on the target receptor. Bioactive compounds of Mimosa pudica have relatively good interactions in inhibiting C. albicans Sap 3